A geographical analysis of the ethnographic composition of the population of Sulaimani province and its reflection on the identity of the Kurdish nation in the Kurdistan Region - Mirza, Dr. Huraman Kamal; Mohammed, Dr.Hemn Nasruddin; Abdullah, Dr.Miqdad Omar; Talib, Prof.Dr.Jaza Tofiq (Sulaimani Journal for Humanities, 2025)
The title of the research is (A Geographical Analysis of the Ethnographic Composition of the Population of Sulaymaniyah Governorate and its Reflection on the Identity of the Kurdish Nation in the Kurdistan Region). The research focuses on Sulaymaniyah Governorate, which is located in northeastern Iraq and eastern Kurdistan Region. The importance of this research lies in its focus on analyzing the size and composition of the ethnographic groups in the governorate from both ethnic and religious perspectives, in addition to studying the role of Kurdish national identity in the Kurdistan Region. The research employs an analytical and comparative methodology, and the research plan is divided into preliminary and research sections, and two main sections. The first section addresses changes in the size and growth of the population of Sulaymaniyah Governorate, while the second section focuses on the ethnographic structure from the perspective of ethnic and religious composition in Sulaymaniyah Governorate. The results of the study showed that, with regard to the ethnicity and religion of the Kurdish nation at the level of the Kurdistan Region, a number of suggestions were made.
Keywords: Ethnography; Evolution; Nation; Religion; Size; Sulaimaniyah Governorate